PELATIHAN PENGENDALIAN ARUS KAS (CASH FLOW) DAN PEMISAHAN KEUANGAN USAHA DENGAN KEUANGAN PRIBADI DI KELURAHAN RAWA BUAYA, KOTA JAKARTA BARAT - Dewi Sulistyani; Didi Sukardi; Rahmatullah Rahmatullah; I Nyoman Suri Adnyana; Radita Arindya; Murdiyono Murdiyono (Nusantara Hasana Journal, 2022)
This community service activity aims to increase the understanding of micro-business owners and the community in Rawa Buaya Village regarding the importance of cash flow management and the separation of business and personal finances. The main problems faced by participants were the lack of regular financial records, the mixing of business and personal funds, and the low ability to manage business cash flow. The activity was implemented through lectures and question-and-answer discussions. The material provided included basic cash flow concepts, techniques for recording income and expenses, preparing simple reports, and strategies for separating business and personal accounts. The results of the activity showed that participants understood the importance of cash flow management in maintaining business continuity and were able to implement simple financial record keeping in a more disciplined manner. This activity is expected to help MSME owners improve their business financial stability and support more accurate business decision-making.